Assessment and management of tic disorders and Tourette syndrome by Australian paediatricians. (17th June 2019) - Efron, Daryl; Payne, Jonathan; Gulenc, Alisha; Chan, Eunice
Abstract : Aim: The diagnosis and management of tic disorders and Tourette syndrome (TS) can be challenging. A better understanding of current approaches by paediatricians is important to inform research and education to improve patient outcomes. We aimed to investigate current assessment and management practices for tics/TS by Australian paediatricians. Methods: An online survey was sent to members of the Australian Paediatric Research Network. Primary outcomes of interest included assessment processes, referrals, behavioural interventions and pharmacological management. Four scenarios were presented to elicit information regarding treatment of different types of cases. Results: Of 340 eligible paediatricians, 139 (41%) responded, with 116 (84%) reporting that they diagnose and manage tics/TS as part of their practice. Questionnaires were used more to identify comorbidities (43%) than to quantify tics (12%). Referrals were most likely to be made to psychologists. Medication was considered important in the management of TS by 45% of respondents, with clonidine identified as the first‐choice medication by 69%. There was wide variation in both the pharmacological and behavioural management strategies reported. Conclusions: There is substantial practice variation among Australian paediatricians in the assessment and management of patients referred with tics/TS. This may reflect insufficient evidence regarding best practice, as well as limited training in this area. There is a need for improved education of Australian paediatricians in the assessment and management of tics/TS, as well as further research to identify optimal treatments.